Menu labeling in Malaysia: who reports noticing and using it? - Rahmat, Syafiqah; Arendt, Susan W. (Research Publishing Academy, 2020)
Menu labeling is provided to help consumers make informed choices when eating out. This study investigated the likelihood of consumers noticing and using menu labeling in restaurants as well as the difference in actual purchase behaviour between consumers who used menu labeling and those who did not. Data collection was conducted in two restaurants that voluntarily offer menu labeling. A total of 580 consumers completed a questionnaire and checklist indicating food items they purchased. Multivariable logistic regression was conducted to estimate adjusted odds ratios (AOR) and 95% confidence intervals (CIs) for consumers noticing and using menu labeling. A bivariate analysis was used to compare consumers’ actual purchase behaviour between those who reported using and not using menu labeling. Individuals with monthly incomes MYR 4,000 to MYR 4,999 were more likely to notice menu labeling than those with monthly incomes less than MYR 1,000. Whereas, individuals 30 to 39 years old, not reporting excellent health status, and not always searching for calorie labeling were significantly less likely to use menu labeling. There were no significant difference in actual purchase behavior between those who reported using and not using menu labeling.